Colonial girlhood in literature, culture and history, 1840-1950 - Moruzi, Kristine; Smith, Michelle J., 1979- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2014)
"Colonial Girlhood in Literature, Culture and History, 1840-1950 explores a range of real and fictional colonial girlhood experiences from Jamaica, Mauritius, South Africa, India, New Zealand, Australia, England, Ireland, and Canada to reflect on the transitional state of girlhood between childhood and adulthood. The interconnected themes of colonialism, empire, gender, race, and class show how colonial girls occupy ambivalent positions in British and settler societies between 1840 and 1950. Although girlhood is often linked to freedom, independence, novelty, and modernity, it may also represent an idea that needs to be contained and controlled to serve the needs of the nation. Across national boundaries, the malleability of colonial girlhoods is evident. Drawing on a range of approaches including history, anthropology, and literary and cultural studies, this book reflects on the complexities of girlhood during the colonial era. "--
Machine generated contents note: -- List of IllustrationsAcknowledgementsNotes on the Contributors1.Colonial Girlhood/Colonial Girls; Kristine Moruzi and Michelle J. Smith PART I: THEORISING THE COLONIAL GIRL 2.Colonialism: What Girlhoods Can Tell Us; Angela Woollacott3.Fashioning the Colonial Girl: 'Made in Britain' Femininity in the Imperial Archive; Cecily DevereuxPART II: ROMANCE AND MARRIAGE4.'Explorations in Industry': Careers, Romance, and the Future of the Colonial Australian Girl; Ken Gelder and Rachael Weaver 5.Deflecting the Marriage Plot: The British and Indigenous Girl in 'Robina Crusoe and Her Lonely Island Home' (1882-1883); Terri Doughty6.Coming of Age in Colonial India: The Discourse and Debate over the Age of Consummation in the Nineteenth Century; Subhasri GhoshPART III: RACE AND CLASS7. 'My blarsted greenstone throne!': Maori Princesses and Nationhood in New Zealand Fiction for Girls; Clare Bradford 8. Black Princesses or Domestic Servants: The Portrayal of Indigenous Australian Girlhood in Colonial Children's Literature; Juliet O'Conor9. The Jam and Matchsticks Problem: Working-Class Girlhood in Late Nineteenth-Century Cape Town; Sarah DuffPART IV: FICTIONS OF COLONIAL GIRLHOOD10. The Colonial Girl's Own Papers: Girl Authors, Editors, and Australian Girlhood in Ethel Turner's Three Little Maids; Tamara S. Wagner11. 'I am glad I am Irish through and through and through': Irish Girlhood and Identity in L.T. Meade's Light O' the Morning; or, The Story of an Irish Girl (1899); Beth Rodgers12. Making Space for the Irish Girl: Rosa Mulholland and Irish Girls in Fiction at the Turn of the Century; Susan Cahill13. Education and Work in Service of the Nation: Canadian and Australian Girls' Fiction, 1908-1921; Kristine Moruzi and Michelle J. SmithPART V: MATERIAL CULTURE14. Picturing Girlhood and Empire: The Guide Movement and Photography; Kristine Alexander15. Material Girls: Daughters, Dress, and Distance in the Trans-Imperial Family; Laura Ishiguro16.An Unexpected History Lesson: Meeting European 'Colonial Girls' through Knitting, Weaving, Spinning, and Cups of Tea; Fiona P. McDonaldBibliographyIndex.
Includes bibliographical references (pages 245-260) and index.
Keywords: Colonies in literature; Girls in literature; Girls -- Books and reading; LITERARY CRITICISM / African; LITERARY CRITICISM / Australian & Oceanian; LITERARY CRITICISM / Caribbean & Latin American; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh